Re-defining ‘Reading’ in the 21st Century: Accessing Multimodal Texts - Chia, Alexius; Chan, Caroline (Beyond Words, 2017)
The act of reading has been made more complex in the 21st century with the proliferation of multimodal texts. Organizations like the ‘Partnership for 21st Century Skills’ and researchers like the New London Group (1996), Hull & Nelson (2005) and Kress et al (2006) argue for the need for schools to re-look at the ways our children become literate in this and media-driven environment. Teachers too live with this reality and can appreciate the fact that not everything they learn can be found in the textbook. However, many do not possess the knowledge and skills to harness the media and technological tools for use in the language classroom. In order for teachers and learners to be effective users of texts in the 21st Century, we argue that a framework is needed to assist them. Hence this article proposes a framework called the 6 Semiotic Modes (Chan & Chia, 2014 adapted from Anstey and Bull, 2010). They include Linguistic, Audio, Spatial, Oral, Visual and Gestural modes and are used as tools to unlock the meaning behind different types of multimodal texts needed for teaching and learning.